Fruit sale strategy with the lowest price sorakan (cheering) in the view of Fiqh Muamalah - Arianti, Farida; Asmadia, Tezi; Leli, Maisarah (Faculty of Law, University of Muhammadiyah Malang, 2022)
Cheering the smallest price of several piles of fruit prices is a fruit-selling strategy to get more consumers. This study aims to understand the description of the smallest price cheers on the fruit sales strategy against the view of fiqh muamalah. What attracts buyers so that they decide to buy and how their interest is raised by hearing price cheers. This is field research conducted in Batusangkar Market. The research employed qualitative descriptive research methods and the research data were obtained from sellers and fruit buyers who shout the smallest price cheer. Data retrieval techniques used in-depth interviews and direct observation of buyers. Interviews were conducted face-to-face with the informants until the same information was obtained. The results show that the strategy of cheering the lowest price from several prices based on piles of fruit quality serves as a driving force and attracts consumers. This strategy is closer to bay' najasy which can drive buyers to buy their merchandise. Therefore, buyers or sellers must ensure that the price they are shouting represents the fruit piles that are visible. When a buyer approaches the place of merchandise, he/she could clearly see the goods being traded.